Social integration and associational behaviour of male Asian elephants in northwest India: a new social learning - Kanchan Puri; Ritesh Joshi; Abhishek K Singh (Mammalogy Notes)
It has been widely acknowledged that adolescent male African elephants (Loxodonta africana) associate with other male elephants after leaving their natal family units, which facilitates in learning social behaviour and surviving in adverse environmental conditions. This aspect has been less studied in Asian elephants (Elephas maximus) and studies on male-male interactions are scarce. Social integration of adolescent males with other male Asian elephants, living either solitary or in small all-male elephant groups is a dynamic process that occurs over a period of several years. This study elucidates the behaviour of an adolescent male Asian elephant and its integration into an all-male group. Further, this study also explains a long-term association of male Asian elephants, which has not been reported previously from the region. The study aims to observe the behaviour of male Asian elephants during the adolescence stage, as well as to observe male-male interactions and long-term associations. We conducted the study in Chilla forest range of the Rajaji National Park and adjacent forests, namely, Haridwar and Lansdowne forest divisions, respectively. Observations spanned over a period exceeding more than a decade from 2006 to 2017, focusing on adolescent behaviour between 2007 and 2011 and male-male associations from 2006 to 2017. We propose that this study is a first ever report in context of behavioural learning in male Asian elephants in northwest India.